Double synonymous mutations in exon 9 of the Cullin3 gene restore exon inclusion by abolishing hnRNPs inhibition. Issue 23 (7th July 2022) - Liu, Zhiying; Sui, Aihua; Wang, Sai; Cui, Li; Xin, Qing; Zhang, Ruixiao; Han, Yue; Shao, Leping; Zhao, Xiangzhong
Abstract: All mutations in exon 9 of the Cullin3 gene associated with pseudohypoaldosteronism type II (PHA II) contribute to exon skipping to different degrees, but the specific molecular mechanism of this aberrant splicing is still unclear. The aims of this study were to investigate the regulatory mechanism underlying two synonymous splicing events, c.1221A > G (p. Glu407Glu) and c.1236G > A (p. Leu412Leu), and to discover a therapeutic strategy for correcting this aberrant splicing by targeting potential regulatory sites. Through a series of RNA pulldown, silver staining, western blotting, small interfering RNA knockdown, in vitro overexpression and single or double site-directed mutagenesis experiments, we first explored the pathogenesis of exon 9 skipping caused by mutations in the CUL3 gene and verified that the main splicing regulators associated with the synonymous c.1221A > G and c.1236G > A mutations were heterogeneous nuclear ribonucleoproteins. In addition, we verified that introducing another synonymous mutation, c.1224A > G (A18G), significantly rescued the abnormal splicing caused by c.1221A > G and c.1236G > A, highlighting the therapeutic potential for the treatment of PHA II.